Regulation of the Coral-Associated Bacteria and Symbiodiniaceae in Acropora valida Under Ocean Acidification - Ge, Ruiqi; Liang, Jiayuan; Yu, Kefu; Chen, Biao; Yu, Xiaopeng; Deng, Chuanqi; Chen, Jinni; Xu, Yongqian; Qin, Liangyun (Frontiers in Microbiology, 2021)
Ocean acidification is one of many stressors that coral reef ecosystems are currently contending with. Thus, understanding the response of key symbiotic microbes to ocean acidification is of great significance for understanding the adaptation mechanism and development trend of the whole coral holobionts. Here, high-throughput sequencing technology was employed to investigate the coral-associated bacteria and Symbiodiniaceae of the ecologically important coral Acropora valida exposed to different pH gradients. After 30 days of acclimatization, we set 4 acidification gradients (pH 8.2, 7.8, 7.4 and 7.2 respectively), each pH condition was applied for 10d, with the whole experiment lasting for 70d. Although the Symbiodiniaceae density decreased significantly, the coral did not appear to be bleached, and the real-time photosynthetic rate did not change significantly, indicating that A. valida has strong tolerance to acidification. Moreover, the Symbiodiniaceae community composition was hardly affected by ocean acidification, with the C1 (Cladocopium goreaui) subclade being dominant among the Symbiodiniaceae dominant types. The relative abundance of the Symbiodiniaceae background types was significantly higher at pH 7.2, indicating that ocean acidification might increase the stability of the community composition by regulating the Symbiodiniaceae rare biosphere. Furthermore, the stable symbiosis between the C1 subclade and coral host may contribute to the stability of the real-time photosynthetic efficiency. Finally, concerning the coral-associated bacteria, the stable symbiosis between Endozoicomonas and coral host is likely to help them adapt to ocean acidification. The significant increase in the relative abundance of Cyanobacteria at pH 7.2 may also compensate for the photosynthesis efficiency of a coral holobiont. In summary, this study suggests that the combined response of key symbiotic microbes help the whole coral host resist the threats of ocean acidification.